Violence risk and emotional dependency in adulthood: a systematic mapping - Alva Pacheco, Alison Margaret (2023)
The main objective of this systematic mapping research was to identify scientific publications on violence and emotional dependence in the last two years. The methodology used consisted of a search for documents in the following databases: Web of Science, Scopus through the search "risk* of violence* AND emotion* depend*", and for Scielo and The Reference "Violence Emotional dependence". Where 19 research studies were found, which comprise articles, master's theses and doctoral dissertations. It was found that most of the research has been conducted in Latin America, especially in Peru, where the Emotional Dependence Questionnaire (CDE) of Lemos and Londoño and the Emotional Dependence Inventory (IDE) have been used, with regard to the violence variable, different types of instruments are used. It could be detected that in a large part of the explorations there is a close connection between violence and emotional dependence, producing problems in the integral health of the person. It should be emphasized that none of the research belongs to quartile level one, which would lead to the conclusion that it would be beneficial to carry out innovative research on this topic in order to optimize future studies on couple relationships.